Characterization of Probiotic Jelly Drinks with Addition of Lactobacillus plantarum (SK5) from Bekasam during Storage - Susi Merry Marini; Desniar Desniar; Joko Santoso (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractLactic acid bacteria from bekasam has potential as an antimicrobial and enzyme producer, as well as probiotics. The purpose of this study were to get the selected formula of the jelly drink with the addition of carrageenan by organoleptic and determine the effect of adding wet biomass (WB) and dry biomass (DB) Lactobacillus plantarum (SK5) from bekasam against chemical and microbiological parameters jelly beverage probiotics during storage. This study consisted of two phases where a preliminary study to determine the best carrageenan concentration and primary research to determine the chemical and microbiological characteristics jelly drink probiotics during storage. Concentrations of carrageenan used were 0.67%; 1% and 1.34%. The best concentration obtained from the preliminary study was 0.67%. The pH of WB during storage decreased to 2.29; total microbial 0.91 log cfu/g; BAL total of 0.2 log cfu/g; dietary fiber 1.26% and 0.53% total sugars. Dry biomass characterization during storage decreased to pH of 2.54; Microbial total of 3.13 log cfu/g; LAB total of 2.22 log cfu/g, while the increase of the dietary fiber of 2.13% and total sugars 1.96%.